Crop canopy and yield of grain legumes in relation to splash erosion in southeastern Rajasthan - PRASAD, ARJUN; PARSAD, S N; SINGH, K D (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted at Kota, Rajasthan during rainy season (July-October) of 1993-96 to evaluatethe performance of short duration and quick growing promising 10 varieties of 3 grain legumes; cowpea (Vignaunguiculata (L.) Walp.) 'C 152', 'RC 19', 'RC 48' and 'RC 80'; greengram (Phaseolus radiatus L.) 'K 851' 'Pusa 105'and 'ML 131'; blackgram (Phaseolus mungo L.) 'Type 9', 'Pant U 19' and 'Pant U 30' in relation to canopy cover,leafarea, splash-erosion, yield and economics. 'C 152' cowpea attained the maximum crop canopy (62.6%), leaf area (947cm2), grain yield (757 kg/ha), net return (Rs 5 894/ha) and benefit: cost ratio (Rs 3.02). The minimum splash erosionwas observed for 'C 152' cowpea than that in other varieties of crops, viz cowpea, greengram and blackgram.